Deletion of an immune evasion gene, steD, from a live Salmonella enterica serovar Typhimurium vaccine improves vaccine responses in aged mice - Allen, Jessica C.; Natta, Shanaliz S.; Nasrin, Shamima; Toapanta, Franklin R.; Tennant, Sharon M. (Frontiers in Immunology, 2024)
Introduction: Non-typhoidal Salmonella (NTS) generally causes self-limiting gastroenteritis. However, older adults (≥65 years) can experience invasive disease and higher hospitalization and case fatality rates due to NTS infection. We have previously shown that CVD 1926 (I77 ∆guaBA ∆clpP ∆pipA ∆htrA) was immunogenic in adult but not aged mice. Here we describe a modified live attenuated vaccine strain harboring a deletion in steD, a Salmonella effector responsible for host immune escape, which we hypothesized would be more immunogenic in aged mice. Methods: Mel Juso and/or mutuDC cells were infected with S. Typhimurium I77, CVD 1926, and their respective steD mutants, and the MHC-II levels were evaluated. Aged (18-month-old) C57BL/6 mice received two doses of PBS, CVD 1926, or CVD 1926 ∆steD perorally and the number of FliC-specific CD4 + T cells were determined. Lastly, aged C57BL/6 mice received three doses of PBS, CVD 1926, or CVD 1926 ∆steD perorally and then were challenged perorally with wild-type S. Typhimurium SL1344. These animals were also evaluated for antibody responses. Results: MHC-II induction was higher in cells treated with steD mutants, compared to their respective parental strains. Compared to PBS-vaccinated mice, CVD 1926 ∆steD elicited significantly more FliC-specific CD4 + T cells in the Peyer's Patches. There were no significant differences in FliC-specific CD4 + T cells in the Peyer's patches or spleen of CVD 1926versus PBS-immunized mice. CVD 1926and CVD 1926 ∆steD induced similar serum and fecal anti-core and O polysaccharide antibody titers after three doses. After two immunizations, the proportion of seroconverters for CVD 1926 ∆steD was 83% (10/12) compared to 42% (5/12) for CVD 1926. Compared to PBS-immunized mice, mice immunized with CVD 1926 ∆steD had significantly lower S. Typhimurium counts in the spleen, cecum, and small intestine upon challenge. In contrast, there were no differences in bacterial loads in the tissues of PBS-vaccinated and CVD 1926-immunized animals. Conclusion: These data suggest that the steD deletion enhanced the immunogenicity of our live attenuated S. Typhimurium vaccine. Deletion of immune evasion genes could be a potential strategy to improve the immunogenicity of live attenuated vaccines in older adults.